Large-scale tethered function assays identify factors that regulate mRNA stability and translation - Luo, En-Ching; Nathanson, Jason L.; Tan, Frederick E.; Schwartz, Joshua L.; Schmok, Jonathan C.; Shankar, Archana; Markmiller, Sebastian; Yee, Brian A.; Sathe, Shashank; Pratt, Gabriel A.; Scaletta, Duy B.; Ha, Yuanchi; et al. (Nature structural & molecular biology, 2020)
The molecular functions of the majority of RNA-binding proteins (RBPs) remain unclear, highlighting a major bottleneck to a full understanding of gene expression regulation. Here, we develop a plasmid resource of 690 human RBPs that we subject to luciferase-based 3ʹ-untranslated-region tethered function assays to pinpoint RBPs that regulate RNA stability or translation. Enhanced UV-cross-linking and immunoprecipitation of these RBPs identifies thousands of endogenous mRNA targets that respond to changes in RBP level, recapitulating effects observed in tethered function assays. Among these RBPs, the ubiquitin-associated protein 2-like (UBAP2L) protein interacts with RNA via its RGG domain and cross-links to mRNA and rRNA. Fusion of UBAP2L to RNA-targeting CRISPR–Cas9 demonstrates programmable translational enhancement. Polysome profiling indicates that UBAP2L promotes translation of target mRNAs, particularly global regulators of translation. Our tethering survey allows rapid assignment of the molecular activity of proteins, such as UBAP2L, to specific steps of mRNA metabolism. A survey of human RNA-binding proteins based on luciferase-based 3ʹ-untranslated-region tethered function assays and identification of their target mRNAs provides insights into their role in RNA metabolism.